2022
DOI: 10.3390/ejihpe12080074
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Adaptation, Self-Efficacy, and Metacognitive Skills in Italian Adolescents with Specific Learning Disorders: A Cross-Sectional Study

Abstract: This study aimed to explore interpersonal adaptation, generalized self-efficacy, and metacognitive skills in a sample of Italian adolescents with and without a specific learning disorder (SLD). A total of 564 secondary and high school students (males = 236; females = 328; age range: 11–19; M = 16.14, SD = 1.70) completed a set of standardized tests assessing social and interpersonal skills (non-affirmation, impulsiveness, narcissism, social preoccupation, and stress in social situations), general self-efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
1
7
0
1
Order By: Relevance
“…In my view such an approach will not only reflect an academic trait but will also encourage students towards optimal engagement and reflection for metacognitive learning. 11,[16][17][18] The response from ChatGPT to all the queries used in this study was minimal in word count, while I am assuming with advancement in technology this shortcoming will be overcome and ChatGPT will indeed be able to write a 10K words response. Based on the observation from this study I am also assuming that with increase in the quantity of response from ChatGPT, the nature of errors observed in this study will also increase, which in my view again will be inadequate to supersede a response from well trained and knowledgeable biological intelligence.…”
Section: Discussionmentioning
confidence: 91%
“…In my view such an approach will not only reflect an academic trait but will also encourage students towards optimal engagement and reflection for metacognitive learning. 11,[16][17][18] The response from ChatGPT to all the queries used in this study was minimal in word count, while I am assuming with advancement in technology this shortcoming will be overcome and ChatGPT will indeed be able to write a 10K words response. Based on the observation from this study I am also assuming that with increase in the quantity of response from ChatGPT, the nature of errors observed in this study will also increase, which in my view again will be inadequate to supersede a response from well trained and knowledgeable biological intelligence.…”
Section: Discussionmentioning
confidence: 91%
“…Positive interpersonal relationships offer emotional support and acknowledgment, hence boosting an individual’s self-confidence. Finally, researchers observed that strong interpersonal interactions can offer emotional support and safety, increasing self-efficacy and decreasing anxiety ( Chenran, 2021 ; Commodari et al, 2022 ). Because the quality of interpersonal relationships impacts an individual’s self-efficacy and anxiety levels, they develop greater confidence in their abilities when they receive support and recognition from others ( Huang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ROBINS-I (Risk of Bias in Non-randomized Studies of Interventions) tool was used to evaluate the risk of bias for all of the other non-randomized studies [43]. Biases were classified into seven domains; namely, (1) bias due to confounding, (2) bias in selection of participants, (3) bias in the classification of interventions, (4) bias due to deviations from the intended interventions, (5) bias due to missing data, (6) bias in the measurement of outcomes, and (7) bias in selection of the reported results. The authors answered signaling questions and utilized the ROBINS-I evaluation table to evaluate the risk in each domain and the overall risk.…”
Section: Study Quality (Risk Of Bias Assessments)mentioning
confidence: 99%
“…However, a significant percentage of the population with disabilities often are not adequately trained in acquiring the skills needed for inclusion, accomplishment, and personal well-being [4]. Among the skills in which a significant deficit is observed are the metacognitive, self-motivation, and emotional intelligence skills [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%